Developing a government enterprise architecture framework to support the requirements of big and open linked data with the use of cloud computing - Lněnička, Martin; Komárková, Jitka (Elsevier, 2019)
Governmental and local authorities are facing many new information and communication technologies challenges. The amount of data is rapidly increasing. The data sets are published in different formats. New services are based on linking and processing differently structured data from various sources. Users expect openness of public data, fast processing, and intuitive visualisation. The article addresses the challenges and proposes a new government enterprise architecture framework. The following partial architectures are included: big and open linked data storage, processing, and publishing using cloud computing. At first, the key concepts are defined. Next, the basic architectural roles and components are specified. The components result from the decomposition of related frameworks. The main part of the article deals with the detailed proposal of the architecture framework and partial views on architecture (sub-architectures). A methodology, including a proposal of appropriate steps, solutions and responsibilities for them, is described in the next step - after the verification and validation of the new framework with respect to the attributes of quality. The new framework responds to emerging ICT trends in order to evolve government enterprise architecture continually and represent current architectural components and their relationships.
Návrh rámce podnikové architektury veřejné správy pro podporu požadavků big a open linked dat s využitím cloud computingu
Keywords: Government enterprise architecture framework; Design science research; Big data; Open linked data; Cloud computing; Quality attributes; ATAM; Methodology; Rámec podnikové architektury veřejné správy; Design science research; Big data; Open linked data; Cloud computing; Atributy kvality; ATAM; Metodika